Courtroom testimony for fingerprint examiners - Daluz, Hillary Moses (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2022)
"Fingerprint examiners today are expected to develop, research, and defend the scientific basis of their conclusions. Recent emphasis, placed on scientific rigor and transparency through documentation, has created a culture shift in the field. Many examiners are baffled by the resulting cultural, procedural, and scientific distinctions, often becoming overwhelmed when required to testify as an expert witness to explain such concepts in the courtroom. Courtroom Testimony for Fingerprint Examiners addresses all aspects of courtroom testimony as the first book to focus solely on testifying on fingerprint evidence as a comparative science. The book is presented in two parts. Part I addresses general expert witnessing for forensic scientists. This serves as a primer for the novice or a review for experienced witnesses covering such topics as: the structure of the criminal justice system and federal rules of evidence, the role of the expert witness, testimony as teaching, presenting challenging scientific concepts to the layperson, court preparation, the three phases of expert witness testimony, and landmark court decisions that have shaped the modern landscape of forensic testimony. Part II focuses on specific issues affecting fingerprint examiners and how to field questions during both direct and cross examination. While such "hot button" topics are absent from currently available texts, this section pays particular attention to these salient, emerging topics. This includes evidentiary challenges to fingerprint evidence, relevant publications such as the PCAST report, nomenclature and standards development, issues surrounding cognitive bias and subjectivity, probability models, error rates, cases of error, and how to address issues of minimum point standards in both the empirical and holistic traditions. Both Part I and Part II provide examples and present innovations applicable to latent and ten-print examiners. As a forensic training instructor for professionals-and previously as a college professor-author Hillary Moses Daluz has spent the past ten years teaching courtroom testimony courses to forensic scientists. Courtroom Testimony for Fingerprint Examiners offers an invaluable resource to forensic scientists, latent print examiners, ten-print examiners, lab personnel in related comparative fields, attorneys, investigative professionals, and students enrolled in forensic science university programs"--
The Criminal Justice System -- The Forensic Expert -- Testimony as Teaching -- Preparing for Court -- Pretrial Matters and Discovery -- In the Courtroom -- Landmark Court Decisions -- Evidentiary Challenges to Friction Ridge Evidence -- Relevant Publications -- Standards Development and Nomenclature Information Classification : General -- Subjectivity and Bias -- 12 Quantitative Considerations -- Cases of Error and Ethical Considerations.
OCLC-licensed vendor bibliographic record.
Keywords: Fingerprints; Evidence, Expert -- United States; Forensic scientists -- United States -- Handbooks, manuals, etc; POLITICAL SCIENCE / Political Freedom & Security / Law Enforcement; SOCIAL SCIENCE / Criminology